DESIGN OF SMART URBAN FARMING BASED ON THE INTERNET OF THINGS USING RASPBERRY PI 4 TO SUPPORT THE REALIZATION OF FOOD SELF-SUFFICIENCY - Lustyana, Astuteryanti Tri; Wahyudi, Slamet; Fanani, Angga Akbar (Industrial Engineering Department, Faculty of Engineering, Universitas Brawijaya, 2026)
Urban agriculture could be a response to limited land availability, access to food, and increasing need for local food production in highly populated cities. However, rooftop farming is subject to temperature differences, water limits, and limited operator supervision and needs constant monitoring. In this study, a pilot-scale smart urban farming system comprising a rooftop greenhouse, water recycling mechanism, drip irrigation, Raspberry Pi 4-based sensing and control, Firebase cloud database and Django online interface was constructed and evaluated. The system was put on the roof of Universitas Brawijaya, Industrial Engineering Building. Functional testing, sensor-to-cloud transmission, dashboard verification, and irrigation discharge measurements were used for performance evaluation. During a 24-h test with a sampling interval of 5 s, 15,443 of the 17,280 predicted records were successfully received, resulting to an upload success rate of 89.37%, a missing-data rate of 10.63% and an average interval of 5.59 s. Some 50,000 recordings were processed over the five-day monitoring period of the greenhouse. A five minute pump operation delivered roughly 32 mL per dripper, i.e. 0.1067 mL/s and the reaction delay between the first and the last dripper was between 20 and 26 seconds. The results indicate that the system can provide real-time monitoring and simple automation for small rooftop gardening.